Solid‐Supported Membrane (SSM)‐Based Electrophysiology Assays Using Surface Electrogenic Event Reader Technology (SURFE²R) in Early Drug Discovery. Issue 3 (13th March 2023) - Pommereau, Antje; Licher, Thomas; Bärenz, Felix
Abstract: This article presents detailed descriptions of procedures and troubleshooting tips for solid‐supported membrane (SSM)‐based electrophysiology assays (SURFE²R) to measure electrogenic solute carrier transporter proteins (SLCs) and assess the effects of compounds that modulate their activity. SURFE²R allows the use of the standard 96‐well format, making it an ideal platform for tertiary assays in a drug‐discovery campaign. The assays are performed with cell‐line‐derived membrane fractions or proteoliposomes containing the transporter of interest. Three main protocols are described for the isolation of membrane fractions from cell culture and the generation of proteoliposomes containing the transporter of interest. Additionally, detailed protocols for SURFE²R single concentration and dose‐response experiments are included to measure the potencies of test compounds in stimulating or inhibiting transporter function (EC50 or IC50 values, respectively) and kinetic functional assays to calculate apparent affinity ( k M ) and maximal velocity ( V max ) of substrate uptake. © 2023 Sanofi. Current Protocols published by Wiley Periodicals LLC. This article was corrected on 23 March 2023. See the end of the full text for details. PROTOCOL GROUP 1 : Sample preparation for SSM‐based electrophysiology assays Support Protocol 1 : Production of cell batches Support Protocol 2 : Simple isolation of cell membranes Alternate Protocol 1 : Isolation of cell membranes with sucrose gradient pre‐purification Support Protocol 3 : Production and isolation of liposomes Support Protocol 4 : Preparation of sensor with isolated cell membranes Alternate Protocol 2 : Preparation of sensor with isolated proteoliposomes PROTOCOL GROUP 2 : Determination of assay parameters for SSM‐based electrophysiology assay Support Protocol 5 : Assay with stable buffer Alternate Protocol 3 : Assay with ion gradient Support Protocol 6 : Determination of membrane/liposome concentration Support Protocol 7 : Determination of substrate dependency k M PROTOCOL GROUP 3 : Determination of advanced assay parameters for SSM‐based electrophysiology assays Support Protocol 8 : Assessment of ion concentration dependency Support Protocol 9 : Assessment of pH dependency Support Protocol 10 : Assessment of DMSO dependency Support Protocol 11 : Assessment of signal stability with multiple activations PROTOCOL GROUP 4 : Compound testing through SSM‐based electrophysiology assays using SURFE²R apparatus Support Protocol 12 : Assessment of signal specificity of a published inhibitor or unknown compound(s) Support Protocol 13 : Compound wash‐out Support Protocol 14 : Statistical analysis